Central hypogonadism due to a giant, "silent" FSH-secreting, atypical pituitary adenoma: effects of adenoma dissection and short-term Leydig cell stimulation by luteinizing hormone (LH) and human chorionic gonadotropin (hCG). (3rd April 2017) - Santi, Daniele; Spaggiari, Giorgia; Casarini, Livio; Fanelli, Flaminia; Mezzullo, Marco; Pagotto, Uberto; Granata, Antonio R. M; Carani, Cesare; Simoni, Manuela
Abstract: We present a case report of an atypical giant pituitary adenoma secreting follicle-stimulating hormone (FSH). A 55-year-old patient presented for erectile dysfunction, loss of libido and fatigue. The biochemical evaluation showed very high FSH serum levels in the presence of central hypogonadism. Neither testicular enlargement nor increased sperm count was observed, thus a secretion of FSH with reduced biological activity was supposed. The histological examination after neuro-surgery showed an atypical pituitary adenoma with FSH-positive cells. Hypogonadism persisted and semen analyses impaired until azoospermia in conjunction with the reduction in FSH levels suggesting that, at least in part, this gonadotropin should be biologically active. Thus, we hypothesized a concomitant primary testicular insufficiency. The patient underwent short-term treatment trials with low doses of either recombinant luteinizing hormone (LH) or human chorionic gonadotropin (hCG) in three consecutive treatment schemes, showing an equal efficacy in stimulating testosterone (T) increase. This is the first case of atypical, giant FSH-secreting pituitary adenoma with high FSH serum levels without signs of testicular hyperstimulation, in presence of hypogonadism with plausible combined primary and secondary etiology. Hypophysectomized patients may represent a good model to assess both pharmacodynamics and effective dose of LH and hCG in the male.